Increasing Regional Cooperation to Promote Infrastructure Development Among Southeast Asian Countries - Miraj, Perdana; Zulkarnain, Zulkarnain; Muslim, Fadhilah (UI Scholars Hub, 2019)
South East Asia has transformed from low economic income into prospectus global economic player during the last decades through industrialization strategies, human capital expansion, and infrastructure investment. Many cities in this region promote infrastructure development across various sectors for instance roads, railways, ports, and airports. This attempt expected to improve accessibility, inter-regional connectivity among cities in the country and significantly reduce logistics costs in the longer term. Improving the level of competitiveness through this action is, therefore, crucial to level up other developed countries in term of economic activities. Despite a growing number of development in developing countries, several challenges are facing the global community today. Cities in South East Asia are now more vulnerable to catastrophic events. Earthquake followed by tsunami and liquefaction in Palu, Sulawesi Island in earlier months reminds us on similar events that struck Aceh province and other parts of the region in 2004. Consequently, cities not only those along the coastline but also in the hinterland area, must adopt a sustainable pathway and building a resilience city. The exponential growth of the internet and technology during the past decades shall be used for mitigating natural disaster and generate livable cities for its inhabitant.